Meningkatkan Keputusan Pembelian Ulang: Peran Citra Merek, After Sales Service dan Perceived Value Sebagai Moderasi - Widiasari, Ni Kadek Yuni; Efrata, Tommy Christian (UNHI Press, 2025)
This study aims to determine the effect of brand image and after sales service on repurchase decisions for a house with perceived value as moderation. The research method uses a quantitative approach with data collection using a questionnaire. The number of research samples taken using the provisions of Hair et al. (2021), namely 190 consumers of Ciputra Beach Resort Bali who already own units at this location. Furthermore, hypothesis testing is carried out using structural equation modeling (SEM) using partial least squares (PLS) tools. The results showed that brand image and after sales service had a positive and significant effect on repurchase decisions, while perceived value was unable to moderate the effect of brand image and after sales service on repurchase decisions. The uniqueness of this study lies in its focus, where most previous studies have mostly highlighted aspects of the first purchase decision on a luxury item, while this study provides new insights into the factors that drive consumer loyalty in the property sector. Based on the results of the study, companies need to focus on strengthening brand image and after-sales service quality as the main strategies for building consumer loyalty in luxury goods. This is because consumers in the high-value property segment will prefer to make decisions based on trust in the brand and concrete experience, not just perceived value. This reflects bounded rationality and satisficing decision making as the main reasons for repurchase decisions.